Pengaruh Diskon Terhadap Peningkatan Impulse Buying Pembeli di Toko Sejahtera Kota Parepare - Rusnaena; Arliny, Adinda; Muhammadun, Muzdalifah; Pangestu, Dian Resky (Program Studi Ekonomi Syariah IAIN Parepare, 2022)
This study aims to investigate the effectiveness of discounts on impulse buying at the Sejahtera Store in Kota Parepare. Additionally, the research aims to explore the magnitude of the impulse buying rate at the Prosperous Store in Parepare City and to establish a positive and significant relationship between discount provisions and impulse buying. The research employs a descriptive quantitative method and is conducted at the Sejahtera Store in Parepare City over a period of 31 days. Data collection is carried out using questionnaires, with a sample size of 100 individuals selected from a total population of 12,900. Data analysis includes the utilization of the One Sample T-test, Pearson product-moment correlation test, simple linear regression test, and determination coefficient test. The study findings demonstrate a significant impact of discounts on impulse buying behavior. The test results reveal a positive and statistically significant relationship between discounts and impulse buying at the Prosperous Store in Parepare City. The discounts' influence on impulse buying is estimated to be around 40.3%, while the remaining 59.7% of impulse buying is influenced by factors not examined in this study. In conclusion, the research highlights the importance of discounts in driving impulse buying behavior and provides valuable insights for retailers to optimize their marketing strategies effectively.